Acute pancreatitis of necropsy finding: Review of 5,277 autopsies. Analysis of 59 cases - Milies, Carlos E.; Acosta, Giselle; Gravina, Francisco G.; Rossi Spera, Juan J.; Pino, Juan C.; Rodríguez, Ana María (Cirugía del Uruguay, 1982)
Completing a study dona by the author (CEM) in 1980 about acute pancreatitis, 5277 necropsies of the Hospital de Clínicas are reviewed, analyzing 59 cases of pancreatitis.